Phytochemical and chemotaxonomic study on Ziziphus Jujuba Mill. (Rhamnaceae). (August 2020) - Li, Danqi; Yue, Dandan; Liu, Da; Zhang, Lixin; Song, Shaojiang
Abstract: Fourteen compounds were isolated from fruits of Ziziphus jujuba Mill., including two flavonoids (1 –2 ), one phenolic glycosides (3 ), one lignan (4 ), four phenols (5 –8 ), three alkaloid (9 –10, 14 ), three sesquiterpenoid (11 –13 ). The structures of all the compounds were established by the NMR techniques, as well as by comparison with previously reported data in literature. Compounds 2″-glucosyl-8-C-glucosyl-4′-O-methylapigenin (1 ), 3′, 4′, 5′-trimethoxycinnamyl alcohol (5 ), 2-4-[(1E)-3-Hydroxyprop-1-en-1-yl]-2, 6-dimethoxy-phenoxypropane-1, 3-diol (6 ), 1-(4-Hydroxyphenyl)ethane-1, 2-diol (8 ), (1S, 3S)-1-Methyl-l, 2, 3, 4-tetrahydro- β -carboline-3-carboxylic acid (9 ), (1R, 3S)-1-Methyl-l, 2, 3, 4-tetrahydro- β -carboline-3-carboxylic acid (10 ), grasshopper ketone (12 ), methyl (3R, 5R)-5-methoxy-3-phenylisoxazolidine-5-carboxylate (14 ) were firstly reported from the genus Ziziphus and the family Rhamnaceae. Furthermore, the chemotaxonomic significance of the isolates was discussed. Highlights: A phytochemical investigation on Ziziphus Jujuba Mill. led to the isolation of 14 compounds. Compounds 1, 5–6, 8–10, 12, and 14 were reported from the genus Ziziphus and the family Rhamnaceae for the first time. Compounds 1, 5 –6, 8 –10, 12, and 14 could be used as potential chemotaxonomic markers.